Clinical implications of sex-specific upper reference limits for high-sensitivity cardiac troponin I in myocardial infarction diagnosis - Rubini Giménez, María; Koechlin, Luca; López-Ayala, Pedro; Spagnuolo, Carlos; Boeddinghaus, Jasper; Wildi, Karin; Nestelberger, Thomas; Tkachenko, Hanna; Basic, Daniel; Kaplan, Emel; Formambuh, Jude; Bima, Paolo; et al. (Revista española de cardiología (English ed.), 2025)
It is unclear whether applying sex-specific rather than uniform upper reference limits (URLs) for high-sensitivity cardiac troponin I (hs-cTnI) improves diagnostic equity between women and men with suspected myocardial infarction (MI). We compared the diagnostic performance of these 2 approaches. In an international, prospective, multicenter study of patients presenting with suspected MI, the final diagnosis was centrally adjudicated twice by 2 independent cardiologists using all available information, including serial measurements of hs-cTnI-Architect, once using the uniform URL (26.2 ng/L) and once using sex-specific URLs (women: 15.6 ng/L; men: 34.2 ng/L). The primary outcome was the diagnostic performance of uniform vs sex-specific URLs at presentation for MI. Among 7137 eligible patients, 2434 were women (34%), median age 65 years, and 4703 were men (66%), median age 59 years. Using the uniform URL, 348 women and 880 men were adjudicated as having MI. At presentation, the sensitivity and specificity of hs-cTnI were high and similar in women (77%; 95%CI, 72-81, and 93%; 95%CI, 92-94, respectively) and men (79%; 95%CI, 77-82, and 94%; 95%CI, 93-94). Using sex-specific URLs, the sensitivity and specificity were 85% (95%CI, 81-89) and 91% (95%CI, 89-92) in women vs 74% (95%CI, 71-77), and 95% (95%CI, 94-95) in men (P<.001). Using sex-specific URLs, diagnostic reclassification occurred in 27 patients, 12 women (upgrade to MI) and 15 men (downgrade from MI), representing 0.4%, (95%CI, 0.3-0.6) of all patients. Using a uniform URL for hs-cTnI provides high and similar diagnostic sensitivity and specificity in women and men. Contrary to expectations, sex-specific URLs introduced sex-related disparities. These findings support the use of a uniform rather than sex-specific URL in the diagnosis of MI. Se desconoce si el uso de límites superiores de referencia (LSR) uniformes frente a los adaptados al sexo para la troponina cardiaca I ultrasensible (cTnI-us) podría mitigar las disparidades relacionadas con el sexo en la precisión del diagnóstico del infarto agudo de miocardio (IAM). En un estudio internacional, prospectivo, multicéntrico, de pacientes con sospecha de IAM, el diagnóstico final se adjudicó 2 veces por 2 cardiólogos independientes usando toda la información disponible, incluidos los valores de cTnI-us Architect, una vez con LSR uniformes (26,2 ng/l) y otra con LSR adaptados al sexo (mujeres 15,6 ng/l; varones 34,2ng/l). Los criterios de valoración principales fueron la capacidad diagnóstica de los LSR uniformes y adaptados al sexo para IAM. De los 7.137 pacientes, 2.434 eran mujeres (34%), con una edad media de 65 años, y 4.703 varones (66%), con una edad media de 59 años. Con los LSR uniformes, se identificó a 348 mujeres y 880 varones como IAM. La sensibilidad y especificidad de valores de cTnI-us a su llegada fueron altas y comparables en mujeres (77%; IC95%, 72-81, y 93%; IC95%, 92-94, respectivamente) y varones (79%; IC95%, 77-82, y 94%; IC95%, 93-94). Con LSR adaptados al sexo, la sensibilidad y especificidad fueron del 85 (IC95%, 81-89) y del 91% (IC95%, 89-92) en mujeres frente al 74 (IC95%, 71-77) y al 95% (IC95%, 94-95) en varones (p<0,001). Con los LSR adaptados, se reclasificó, respecto al diagnóstico final, a 27 pacientes: 12 mujeres (nuevo diagnóstico de IAM) y 15 varones (perdieron el diagnóstico de IAM), lo que representa un 0,4% (IC95%, 0,3-0,6) de todos los pacientes. El uso de un LSR uniforme para cTnI-us ofrece una elevada y prácticamente idéntica sensibilidad y especificidad en varones y mujeres. Al contrario de lo esperado, los LSR adaptados al sexo suponen desigualdades entre sexos. Estos datos sugieren continuar usando valores comunes para ambos sexos.